Preparation method of calcium-iron-zirconium composite catalyst for degrading electroplating wastewater
The preparation method for a calcium-iron-zirconium composite catalyst addresses the stability and reusability issues of existing electroplating wastewater treatments by enhancing the catalyst's performance in removing chelated metals, with reduced calcium precipitation, effectively treating electroplating wastewater using next hypochlorous acid oxidation technology.
Patent Information
- Application Number
- CN202411001808.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-03-25
AI Technical Summary
Existing methods for treating electroplating wastewater, such as the use of calcium-iron composite catalysts, face challenges in simultaneously removing chelated metals and improving catalyst stability and reusability, with significant calcium precipitation affecting their effectiveness.
A method for preparing a calcium-iron-zirconium composite catalyst involving solubilization, dispersion, and high-temperature processing steps, using specific molar ratios and additives like PVP K90 and APAM, to enhance the catalyst's stability and efficiency in removing chelated metals from electroplating wastewater.
The method results in a catalyst with improved stability and reusability, effectively removing chelated metals with reduced calcium precipitation, achieving better performance in electroplating wastewater treatment using the next hypochlorous acid oxidation technology.
Smart Images

Figure CN119680552A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater. Background Art
[0002] The electroplating industry is one of the important industrial economic fields in my country. It brings huge economic benefits and also brings more environmental pollution problems. The complex metal in electroplating wastewater is an industry problem. The complete removal of organic ligands and the efficient recovery of heavy metals are difficult to be carried out simultaneously. Hypochlorous acid oxidation technology is widely used in the field of ordinary wastewater treatment, but it is not ideal for the removal of complex metals. The Chinese patent with publication number CN 114797871A discloses a preparation of a calcium-iron composite catalyst for degrading pollutants in electroplating wastewater, which is doped with calcium element to form a calcium-iron composite catalyst, and then allows it to apply the hypochlorous acid oxidation technology to the removal of complex heavy metals in electroplating wastewater. It has a good catalytic effect in the hypochlorous acid oxidation system, but it is found in the later research and development that the stability of the calcium-iron composite catalyst needs to be further improved, and the repetition efficiency is poor, and calcium precipitation is serious during the application process, which affects the actual use effect and needs to be further improved. Therefore, the present invention aims to further develop a preparation method of a calcium-iron-zirconium composite catalyst for degrading electroplating wastewater, so as to better meet actual needs. Summary of the invention
[0003] The technical problem solved by the present invention is to provide a method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater, so as to prepare a calcium iron zirconium composite catalyst that can improve the catalytic degradation of complexed heavy metals in electroplating wastewater while further improving the catalytic stability and repetition efficiency and reducing calcium precipitation.
[0004] The technical problem solved by the present invention is achieved by adopting the following technical solutions:
[0005] A method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater comprises the following steps:
[0006] Dissolution treatment: dissolving calcium salt, zirconium salt and iron salt and then adding the first polymer ion dispersant to obtain solution A;
[0007] Dispersion treatment: add alkaline solution to solution A, stir evenly, add the second polymer ion dispersant, and disperse by ultrasonic to obtain solution B;
[0008] High temperature treatment: Solution B is subjected to high temperature reaction at 200-400° C. for 20-40 minutes. After the high temperature reaction is completed, solid-liquid separation is performed to obtain a precipitate; the precipitate is washed and dried to obtain a calcium iron zirconium composite catalyst.
[0009] Furthermore, in the dissolution treatment step, calcium salt, zirconium salt and iron salt are dissolved in distilled water, and the molar ratio of calcium, zirconium and iron in the solution after dissolution is 4-5:0.5-1.5:1-3.
[0010] Furthermore, the molar ratio of calcium, zirconium and iron in the solution after dissolution is 4:1:2.
[0011] Furthermore, in the dissolution treatment step, the mass ratio of the total amount of calcium salt, zirconium salt and iron salt to distilled water is 1:10-100; the first polymer ion dispersant is PVP K90, and the content of PVP K90 in solution A is 0.1-0.5 g / L; PVP K90 is polyvinyl pyrrolidone.
[0012] Furthermore, the calcium salt is one or more of calcium nitrate, calcium hypochlorite, and calcium carbonate; the zirconium salt is zirconium oxychloride; and the iron salt is one or more of ferric chloride, ferric sulfate, and ferric nitrate.
[0013] Furthermore, in the dispersion treatment step, after adding the alkaline solution to the solution A, magnetic stirring is adopted, and the stirring time is 60 to 120 minutes. After the stirring is stable, the pH of the solution is 7 to 11.
[0014] Furthermore, in the dispersion treatment step, the second polymer ion dispersant is APAM, and the content of APAM in solution B is 0.05-0.5 g / L; APAM is anionic polyacrylamide.
[0015] Furthermore, in the high temperature treatment step, solid-liquid separation is carried out in a centrifuge, and after centrifugation, the precipitate is repeatedly washed with distilled water or anhydrous alcohol solution and then centrifuged; the rotation speed of the centrifuge is 5000-15000 r / min.
[0016] Furthermore, in the high temperature treatment step, vacuum constant temperature drying is used for drying, the drying temperature is 50 to 100° C., and the drying time is 10 to 30 hours.
[0017] A calcium iron zirconium composite catalyst for degrading electroplating wastewater is prepared by any of the above methods.
[0018] Beneficial effects: The preparation method of the calcium iron zirconium composite catalyst for degrading electroplating wastewater described in the present invention has a simple preparation process. After the prepared calcium iron zirconium composite catalyst is applied to electroplating wastewater treatment using hypochlorous acid oxidation technology, it has a good degradation effect on the complexed heavy metals in the electroplating wastewater, and calcium precipitation is greatly reduced, and the repetition efficiency and stability are greatly improved.
[0019] The preparation method of the calcium iron zirconium composite catalyst for degrading electroplating wastewater described in the present invention has different effects on degrading complexed heavy metals during the preparation process. When the molar ratio of calcium iron to zirconium is 4:1:2, the catalytic degradation effect of the calcium iron zirconium composite catalyst is the best.
[0020] The preparation method of the calcium iron zirconium composite catalyst for degrading electroplating wastewater of the present invention is simple, has low requirements on equipment, good operability, and stable material structure in a hypochlorous acid oxidation system. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a SEM image of the calcium iron zirconium composite catalyst material at 1 μm in Example 1 of the present invention;
[0022] Figure 2 is an infrared spectrum of the calcium iron zirconium composite catalyst material in Example 1 of the present invention;
[0023] Figure 3a , Figure 3b , Figure 3c , Figure 3d , Figure 3e They are respectively the XPS test graphs of O, Ca, Fe and Zr of the calcium iron zirconium composite catalyst material in Example 1 of the present invention.
[0024] Figure 4 This is an XRD test diagram of the calcium iron zirconium composite catalyst material in Example 1 of the present invention;
[0025] Figure 5 is the pollutant removal rate of the calcium iron zirconium composite catalytic material at different catalyst dosages in Example 1 of the present invention;
[0026] Figure 6 is the pollutant removal rate of the calcium iron zirconium composite catalytic material in Example 1 of the present invention at different oxidant dosages;
[0027] Figure 7 It is the pollutant removal rate of the iron-zirconium composite catalytic material in Example 1 of the present invention at different times. DETAILED DESCRIPTION
[0028] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0029] Example 1
[0030] A method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater comprises the following steps:
[0031] Dissolution treatment: Mix the raw materials of calcium carbonate, zirconium oxychloride and ferric sulfate with distilled water, and perform ultrasonic treatment until the powder is completely dissolved; the mass ratio of the total amount of calcium salt, zirconium salt and iron salt to distilled water is 1:50; the molar ratio of calcium, zirconium and iron in the solution after dissolution is 4:1:2. Then, PVP K90 is added to the fully dissolved solution to obtain solution A, in which the content of PVP K90 in solution A is 0.3 g / L; magnetic stirring is performed for 30 minutes.
[0032] Dispersion treatment: Slowly add NaOH solution to solution A, and continue stirring by magnetic stirring until the pH value of the solution is 11, the stirring time is about 80 minutes, and then add APAM, and continuously perform ultrasonic dispersion treatment to obtain solution B, the ultrasonic power is preferably 50KHz, and the APAM content in solution B is 0.15g / L;
[0033] High temperature treatment: Place solution B in a high temperature reactor and perform a high temperature reaction at 300°C for 30 minutes. Place the solution after the high temperature reaction in a centrifuge for centrifugation at a speed of 10,000 r / min. After centrifugation, obtain a precipitate. Wash the precipitate with distilled water for multiple times. Centrifuge to obtain the precipitate after each washing. Place the final precipitate in a vacuum drying oven for drying at a drying temperature of 80°C for 20 hours. After drying, a calcium iron zirconium composite catalyst is obtained.
[0034] Example 2
[0035] A method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater comprises the following steps:
[0036] Dissolution treatment: Mix calcium nitrate, zirconium oxychloride and ferric chloride raw materials with distilled water, and perform ultrasonic treatment until the powder is completely dissolved; the mass ratio of the total amount of calcium salt, zirconium salt and iron salt to distilled water is 1:100; the molar ratio of calcium, zirconium and iron in the solution after dissolution is 4.5:1.5:2.5. Then, PVP K90 is added to the fully dissolved solution to obtain solution A; the content of PVP K90 in solution A is 0.35 g / L; magnetic stirring is performed for 30 minutes.
[0037] Dispersion treatment: Slowly add NaOH solution to solution A, and continue stirring by magnetic stirring until the pH value of the solution is 11, the stirring time is about 80 minutes, and then add APAM, and continuously perform ultrasonic dispersion treatment to obtain solution B, the ultrasonic power is preferably 50KHz, and the APAM content in solution B is 0.2g / L;
[0038] High temperature treatment: Place solution B in a high temperature reactor and react at 280°C for 40 minutes. Place the solution after the high temperature reaction in a centrifuge for centrifugation at a speed of 12,000 r / min. After centrifugation, obtain a precipitate. Wash the precipitate with distilled water for multiple times. Centrifuge to obtain the precipitate after each washing. Place the final precipitate in a vacuum drying oven for drying at a drying temperature of 100°C for 15 hours. After drying, a calcium iron zirconium composite catalyst is obtained.
[0039] Example 3
[0040] A method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater comprises the following steps:
[0041] Dissolution treatment: Mix calcium nitrate, zirconium oxychloride and ferric chloride raw materials with distilled water, and perform ultrasonic treatment until the powder is completely dissolved; the mass ratio of the total amount of calcium salt, zirconium salt and iron salt to distilled water is 1:60; the molar ratio of calcium, zirconium and iron in the solution after dissolution is 4.2:0.9:2.2. Then, PVP K90 is added to the fully dissolved solution to obtain solution A, and the content of PVP K90 in solution A is 0.4 g / L;
[0042] Dispersion treatment: Slowly add NaOH solution to solution A, and continue stirring by magnetic stirring until the pH value of the solution is 11, the stirring time is about 80 minutes, and then add APAM, and continuously perform ultrasonic dispersion treatment to obtain solution B; the ultrasonic power is preferably 50KHz, and the content of APAM in solution B is 0.1g / L;
[0043] High temperature treatment: Place solution B in a high temperature reactor and react at 360°C for 28 minutes. Place the solution after the high temperature reaction in a centrifuge for centrifugation at a speed of 12,000 r / min. After centrifugation, obtain a precipitate. Wash the precipitate with distilled water for multiple times. Centrifuge to obtain the precipitate after each washing. Place the final precipitate in a vacuum drying oven for drying at a drying temperature of 50°C for 30 hours. After drying, a calcium iron zirconium composite catalyst is obtained.
[0044] Comparative Example 1
[0045] The difference between this comparative example and Example 1 is that in the dissolution step, after the calcium salt, zirconium salt and iron salt are dissolved, PVP K90 is not added and the dispersion step is entered. The rest is the same as Example 1.
[0046] Comparative Example 2
[0047] The difference between this control example and Example 1 is that APAM is not added in the dispersion treatment step, and the rest is the same as Example 1.
[0048] Comparative Example 3
[0049] Compared with Example 1, this control example is different in that in the dissolution treatment step, the calcium salt, zirconium salt and iron salt are dissolved in distilled water, and the molar ratio of calcium, zirconium and iron in the solution after dissolution is 1:2:4. The rest is the same as Example 1.
[0050] Comparative Example 4
[0051] The difference between this comparative example and Example 1 is that in the high temperature treatment step, solution B is reacted at 80° C. for 30 min, and the rest is the same as Example 1.
[0052] Comparative Example 5
[0053] The calcium-iron composite catalyst is prepared by adopting the technology disclosed in the Chinese patent with publication number CN 114797871 A.
[0054] The calcium iron zirconium composite catalyst prepared in Example 1 was tested.
[0055] like Figure 1 As shown, the calcium iron zirconium composite catalyst prepared by the present invention has a layer block structure. Figure 2 See that 594.2cm -1 The absorption peaks near 1361cm are caused by the stretching vibration of Fe-O, Ca-O, and Zr-O bonds. -1 、819cm -1 The absorption peak near 1632cm is caused by the stretching vibration of Fe-OH bond; -1 The absorption peak that appears nearby is the HOH deformation vibration peak, 3490cm -1 The bands are related to the stretching vibration of surface hydroxyl groups, the -OH vibration of adsorbed water and the bending vibration of Fe-OH, respectively.
[0056] From the O1s spectrum in Figure 3, the three fitting peaks at 529.1eV, 530.2eV, and 531eV can be attributed to the lattice oxygen bound to the metal and the adsorbed oxygen on the oxygen vacancies, respectively. The abundant oxygen vacancies can increase the electron transfer ability of the material surface, thereby improving the catalytic performance. From the Fe2p spectrum, two pairs of spin-orbit double peaks are shown. The double peak orbits contain Fe(Ⅱ) and Fe(Ⅲ). The peaks at 710.8eV and 724.5eV are due to the core energy level of Fe(Ⅱ), and the binding energy at 714eV and 731.6eV are attributed to the existence of Fe(Ⅲ). In the Ca 2p spectrum, the peaks at 345.9eV and 350eV represent Ca2p3 / 2 and Ca2p1 / 2, indicating that the Ca element has been successfully introduced into the material. In the Zr3d spectrum, the peaks at 184eV and 181eV represent Zr3d3 / 2 and Zr3d5 / 2, indicating that the Zr element has been successfully introduced into the material.
[0057] pass Figure 4 It can be seen that the peaks at 2θ of 34.1° and 50.8° correspond to the (001), (102), and (110) crystal planes of Ca-OH (PDF#50-0008), the peaks at 2θ of 29.4° are related to Ca-O (PDF#28-0775), and the peaks at 2θ of 44.5° and 87.9° correspond to the (211) and (251) crystal planes of Zr-O (PDF#49-1746). The enhancement of these peaks indicates that the crystallinity and particle size increase due to the incorporation of Ca and Zr.
[0058] The calcium iron zirconium composite catalyst prepared in Example 1 was applied to the removal of complexed heavy metals in electroplating wastewater. Complexed copper (Cu 2+ The concentration of calcium iron zirconium composite catalyst was 20 mg / L. The dosage of calcium iron zirconium composite catalyst was 0.25 g / L, 0.5 g / L, 0.75 g / L and 1 g / L respectively. Figure 5 It can be seen that when the dosage of calcium iron zirconium composite catalyst is 0.5g / L, the removal rate of complex copper can reach more than 80%. When the dosage of calcium iron zirconium composite catalyst is 0.5g / L, the dosage of sodium hypochlorite oxidant is adjusted to Figure 7 It can be seen that when the dosage of sodium hypochlorite oxidant is 3 ml / L, a 90% removal effect can be achieved in 90 minutes.
[0059] Table 1 shows the treatment results of sewage by the calcium iron zirconium composite catalysts prepared in Examples 1 to 3, Comparative Examples 1 to 4, and the calcium iron composite catalyst prepared in Comparative Example 5. The dosage of the catalyst is 0.5 g / L, the dosage of the sodium hypochlorite oxidant is 3 ml / L, and the reaction time is 90 min.
[0060] Table 1
[0061]
[0062]
[0063] (I) The calcium iron zirconium composite catalyst described in Example 1 and the calcium iron composite catalyst described in Comparative Example 5 were subjected to stability tests.
[0064] Take 100mL water sample of 20mg / L EDTA-Cu into a conical flask, add 0.5g / L Fe-Ca-Zr and Fe-Ca composite catalyst respectively, then add 2.5g / L sodium hypochlorite, react for 90min, then take sample and measure Cu by atomic absorption. 2+ After standing, the supernatant was poured out, and 100 mL of water sample containing 20 mg / L EDTA-Cu was added again, and then 2.5 g / L sodium hypochlorite was added to react for 90 minutes, and then the sample was taken for atomic absorption measurement of Cu.2+ The results are shown in Table 2.
[0065] Table 2
[0066] First time (mg / L) Second time (mg / L) The third time (mg / L) Fourth time (mg / L) Raw water 20.846 19.5725 20.066 20.5725 Fe-Ca-Zr 0.128 0.581 1.519 2.16 Fe-Ca 0.118 0.829 2.7335 3.8015
[0067] It can be seen from Table 2 that the repetitive stability of the calcium iron zirconium composite catalyst of the present invention is better than that of the calcium iron composite catalyst.
[0068] (ii) The calcium iron zirconium composite catalyst described in Example 1 and the calcium iron composite catalyst described in Comparative Example 5 were subjected to calcium precipitation detection.
[0069] Take 100mL of water sample with 20mg / L EDTA-Cu into a conical flask, add 0.5g / L Fe-Ca-Zr and Fe-Ca materials respectively, then add 2.5ml / L sodium hypochlorite to react, and take samples for atomic absorption measurement of Ca at 0min, 15min, 30min, 45min, 60min, 75min, and 90min respectively. 2+ The results are shown in Table 3.
[0070] Table 3
[0071]
[0072] It can be seen from Table 3 that the calcium-iron composite catalyst in the prior art has serious calcium precipitation during the reaction process, while the calcium-iron-zirconium composite catalyst of the present invention has less calcium precipitation during the reaction process and has better performance.
[0073] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater, characterized in that: The steps include: Dissolution treatment: dissolving calcium salt, zirconium salt and iron salt, and then adding the first polymer ion dispersant to obtain solution A; dispersion treatment: adding alkaline solution to solution A, stirring evenly, and then adding the second polymer ion dispersant, and ultrasonically dispersing to obtain solution B; High temperature treatment: Solution B is subjected to high temperature reaction at 200-400° C. for 20-40 minutes. After the high temperature reaction is completed, solid-liquid separation is performed to obtain a precipitate; the precipitate is washed and dried to obtain a calcium iron zirconium composite catalyst.
2. The method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater according to claim 1, characterized in that: In the dissolution treatment step, calcium salt, zirconium salt and iron salt are dissolved in distilled water, and the molar ratio of calcium, zirconium and iron in the solution after dissolution is 4-5:0.5-1.5:1-3.
3. The method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater according to claim 1, characterized in that: After dissolution, the molar ratio of calcium, zirconium and iron in the solution is 4:1:
2.
4. The method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater according to claim 2, characterized in that: In the dissolution treatment step, the mass ratio of the total amount of calcium salt, zirconium salt and iron salt to distilled water is 1:10-100; the first polymer ion dispersant is PVP K90, and the content of PVP K90 in solution A is 0.1-0.5 g / L.
5. The method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater according to claim 1, characterized in that: The calcium salt is one or more of calcium nitrate, calcium hypochlorite, and calcium carbonate; the zirconium salt is zirconium oxychloride; and the iron salt is one or more of ferric chloride, ferric sulfate, and ferric nitrate.
6. The method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater according to claim 1, characterized in that: In the dispersion treatment step, after adding the alkaline solution to solution A, magnetic stirring is adopted for 60 to 120 minutes. After the stirring is stable, the pH of the solution is 7 to 11.
7. The method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater according to claim 1, characterized in that: In the dispersion treatment step, the second polymer ion dispersant is APAM, and the content of APAM in solution B is 0.05-0.5 g / L.
8. The method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater according to claim 1, characterized in that: In the high temperature treatment step, solid-liquid separation is carried out in a centrifuge, and after centrifugation, the precipitate is repeatedly washed with distilled water or anhydrous alcohol solution and then centrifuged; the speed of the centrifuge is 5000-15000r / min.
9. The method for preparing a calcium iron zirconium composite catalyst for degrading electroplating wastewater according to claim 1, characterized in that: In the high temperature treatment step, vacuum constant temperature drying is adopted for drying, the drying temperature is 50-100° C., and the drying time is 10-30 hours.
10. A calcium iron zirconium composite catalyst for degrading electroplating wastewater, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation of calcium-iron composite catalyst for degrading pollutants in electroplating wastewater
CN114797871A